2008
DOI: 10.1111/j.1460-2695.2008.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the modified three‐rail shear test and the [(+45°,−45°)]ns tensile test for pure shear fatigue loading of carbon fabric thermoplastics

Abstract: A B S T R A C T The (three)-rail shear test is rarely considered for testing of fibre-reinforced composites under pure shear fatigue loading conditions because of all experimental difficulties. However, in this article, a carbon fabric-reinforced PPS is tested using a modified three-rail shear test setup. The results are compared with [(+45 • ,−45 • )] 4s tensile tests with good correspondence. All fatigue experiments were done with R = 0 and the influence of maximum shear stress and frequency is investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In a previous study [30], the fatigue behaviour under shear loads has already been discussed. For the tension-tension fatigue tests, the geometry proposed by the D3039/D3039M-00 standard was also considered for specimens with a [(+45°,-45°)] 4s stacking sequence.…”
Section: Fatigue Experiments On [(+45°-45°)] 4s Specimensmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study [30], the fatigue behaviour under shear loads has already been discussed. For the tension-tension fatigue tests, the geometry proposed by the D3039/D3039M-00 standard was also considered for specimens with a [(+45°,-45°)] 4s stacking sequence.…”
Section: Fatigue Experiments On [(+45°-45°)] 4s Specimensmentioning
confidence: 99%
“…The realigning of the fibres can be seen in a detailed image of specimen N2 (see Figure 14) Figure 14 Illustration of the change in fibre orientation due to the softening of the matrix [30].…”
Section: Fatigue Experiments On [(+45°-45°)] 4s Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, they can attain a high degree of crystallinity and are cheaper than PEEK based laminates. However, to date, few studies dealing with the behaviour of carbon fabrics reinforced PPS laminates have been published [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], and these were focused on investigating the effect of temperature, hygrothermal aging and thermal cycling on their mechanical performance. It was found that at temperatures higher than the glass transition of these materials, the quality of the fiber-matrix interfacial adhesion significantly decreased, resulting in reduced mechanical properties particularly under off-axis loading conditions, and their behaviour became highly time-dependent due to the viscoelastic nature of the TP matrix [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%